Saturday

January 31, 2015

January 31, 2015

Posted by **Randy** on Sunday, May 9, 2010 at 7:59pm.

lim 2+6x-3x^2 / (2x+1)^2

x-> - infinity

lim 4n-3 / 3n^2+2

n-> infinity

I did

lim 2+6x-3x^2 / (2x+1)^2

x-> - infinity

(2+6x-3x²)/(4x²+4x+1)

(2/x² + 6/x -3)/(4 + 4/x + 1/x²)

as x-> - infinity. My answer is -3/4

lim 4n-3 / 3n^2+2

n-> infinity

Answer is 0.

- Pre-cal -
**bobpursley**, Sunday, May 9, 2010 at 8:04pmboth are right.

**Answer this Question**

**Related Questions**

Pre-cal - Please determine the following limit if they exist. If the limit doe ...

Calculus, please check my answers! - 1. Evaluate: lim x->infinity(x^4-7x+9)/(...

Calculus help, please! - 1. Evaluate: lim x->infinity(x^4-7x+9)/(4+5x+x^3) 0...

Math - 1. If -1/infinity = infinity or -infinity ? 2. If lim x->infinity^- = ...

Math - 1. If -1/infinity = infinity or -infinity ? 2. If lim x->infinity^- = ...

Check my CALCULUS work, please! :) - Question 1. lim h->0(sqrt 49+h-7)/h = ...

Calc. Limits - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0...

Calculus. Limits. Check my answers, please! :) - 4. lim (tanx)= x->pi/3 -(...

calc - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- ...

Calc Please Help - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/...